Kajian kelayakan lokasi budidaya lobster (Panulirus spp.) di Perairan Desa Pulisan - Noni Saliwati Sarifudin; Winda M. Mingkid; Hariyani Sambali; Suzanne L. Undap; Sammy N.J. Longdong; Ockstan J. Kalesaran (Universitas Sam Ratulangi, 2023)
The aim of this study was to determine the feasibility of the location for cultivating spiny lobsters (Panulirus spp.) in Pulisan Village waters, East Likupang District, North Minahasa Regency. This research was an explorative and descriptive research using primary and secondary data. Primary data was collected through direct observation, site surveys, and interviews, while secondary data was collected from various available sources such as reports, research, books guidebooks, citing records in of Pulisan Village, East Likupang District Office, and various literature. Data were analyzed using descriptive analysis and internal and external factor analysis (SWOT). The results of the analysis showed that the location of spiny lobster cultivation met the SNI 8116 (2015) standard regarding sand spiny lobster (Panulirus pomarus) production. The strength–opportunity strategy is to protect the location and its surroundings where the existing habitat of the spiny lobster occurs, so the production will be gained and therefore the market price will be high. The weakness–opportunity strategy is how government involvement in supporting the development of spiny lobster aquaculture. Next, the strength–threat strategy is to maximize the use of high technology to overcome the unpredictable weather and season. Finally, the weakness–threat strategy is to inspire and encourage local people about the benefits of doing spiny lobster aquaculture and how to overcome any problems. Keywords: SWOT, water quality, aquaculture